Adapting to Change: The Power of Agile Management in Challenging Times - Chaitrali Kale; Pritam Lanjewar; A. Vijayalakshmi; Shirisha Deshpande; Prashant Balwantrao Thakare; Puja S. Agrawal (Metallurgical and Materials Engineering, 2025)
Three examples that demonstrate the necessity of organizational agility in reply to the continued influence of the global COVID-19 pandemic on business have made it clear that adopting and implementing agile management strategies to address uncertainty are critical to any organization’s sustainability and long-term growth. Thus, looking from the relevance of agile in post-pandemic world, this research signifies the way agile management is enabling the businesses with resilience, adaptability and innovation. Analyzing case studies across multiple industries, the study identifies key agile practices, including iterative planning, cross-functional collaboration, and rapid decision-making, that have allowed firms to recover and succeed in a volatile environment. It also extends the literature, exploring how digital transformation, remote work policies and crisis management frameworks converge to embed organizational agility. It indicates that practicing agile methodologies within companies enables them to achieve higher levels of operational efficacy, employee engagement, and responsiveness to the market. The study concludes with actionable strategic recommendations that companies should follow to integrate agility into their organizational culture as a crucial requirement for remaining viable in an age of relentless disruption.